GLC and GLC-MS analysis of thiophene derivatives in plants and in in vitro cultures of Tagetes patula L. (Asteraceae) - Römisch-Margl, Lilla; Tei, Andreas; Wink, Michael (Zeitschrift für Naturforschung. A, a journal of physical sciences, 2014)
The occurrence of thiophenic compounds in diverse plant organs and in in vitro root-, callus- and cell suspension cultures of Tagetes patula cv. Carmen was investigated using capillary GLC and GLC-MS. The separation of thiophenes by capillary GLC and the group specific MS fragmentation with the typical sulfur isotope peaks allowed the unequivocal assignment of individual thiophenes in complex mixtures, even when occurring in traces and in the presence of different geometrical isomers. The extracts of Tagetes patula cv. Carmen contained the following 8 thiophene compounds: 5-(3-buten-1-ynyl)-2,2′-bithienyl (BBT), 5′-methyl-5-(3-buten-1-ynyl)-2,2′-bithienyl (MeBBT), 5-(1-pentynyl)-2,2′-bithienyl (PBT), 5-(4-hydroxy-1-butynyl)-2,2′-bithienyl (BBTOH), 2,2′,5,2″-terthienyl (α-T), 5-(4-acetoxy- 1-butynyl)-2,2′-bithienyl (BBTOAc), 5-methylaceto-5′-(3-buten-1-ynyl)-2,2′-bithienyl (AcOCH2BBT), and 5-(3,4-diacetoxy-1-butynyl)-2,2′-bithienyl (BBT(OAc)2). The most complex thiophene profile, including the less common PBT was detected in aerial parts of freshly harvested plant material. Under in vitro conditions only the root cultures, but not callus or cell suspension cultures produced substantial amounts of irregular thiophenes confirming that roots are the main site of thiophene biosynthesis.
Gesehen am 04.10.2017